Prevalence of asymptomatic Bacteriuria among Pregnant Women in Sirte City (Libya). (Sirte Journal of Medical Sciences, 2022)
Asymptomatic bacteriuria (ASB) is known as significant presence of pathogenic bacteria more as 105 CFU/ml in urine culture of pregnant women without any symptoms indicate of urinary tract infections. Which is may lead to serious complications on health of a pregnant woman, and the fetus if left untreated.The purpose of this study was designed to find the prevalence of asymptomatic urinary tract infection (AUTI) among pregnant women, and also to determine the antibacterial susceptibility of the isolates to various antibiotics to reduce risk factors in pregnancy. However, little is known about asymptomatic bacteriuria in pregnancy in Libya, namely in Sirte city.A total of 265 samples were collected in 7 months study involving women attending antenatal clinics in Sirte City-Libya, mid-stream urine samples were collected for microscopically examination. A colony culture growth were identified by biochemical tests and conventional antibiotic susceptibility tested in microbiology laboratory. Isolates were identified and tested against commonly used antimicrobial drugs using Kirby Bauer disc diffusion method.The prevalence of 265 pregnant women in different age groups were enrolled in this study, only 76 (28.7%) pregnant women had bacteriuria.  The organism isolated from the urine sample according to the frequency of occurrence was Escherichia coli 32(42.1%), Coagulase negative Staphylococcus 11 (14.4%), Staphylococcus aureus 9(11.8%), Klebsiella Pneumoniae 9(11.8%), Streptococcus agalactiae 8 (10.5%), Enterococcus spp 5(6.6%), Proteus mirabilis 2(2.6%), respectively.The overall prevalence of asymptomatic bacteriuria among pregnant women in the study area was not high, but need to be taken on consider reducing risk of infections. The presence of asymptomatic bacteriuria and their antibiotic susceptibility test results should be taken into consideration during the management of pregnant women who are visiting antenatal care clinic; because there was high resistance to the most commonly used antibiotics. Routine urine culture and antimicrobial sensitivity for antenatal women should be carried out to detect asymptomatic bacteriuria to treat early infections, to prevent any serious complication associated with pregnancy.
Keywords: Urinary Tract Infection (UTI); Asymptomatic Bacteriuria (ASB); E. coli, Pregnancy